2022
DOI: 10.3390/life12060785
|View full text |Cite
|
Sign up to set email alerts
|

The Emergence of Embryonic Myosin Heavy Chain during Branchiomeric Muscle Development

Abstract: A prerequisite for discovering the properties and therapeutic potential of branchiomeric muscles is an understanding of their fate determination, pattering and differentiation. Although the expression of differentiation markers such as myosin heavy chain (MyHC) during trunk myogenesis has been more intensively studied, little is known about its expression in the developing branchiomeric muscle anlagen. To shed light on this, we traced the onset of MyHC expression in the facial and neck muscle anlagen by using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…Previously, using double in situ hybridization analysis of whole mount chicken embryos, we reported that Sox10 and Ap2α expression can be used to analyze the respective location of neural crest cells in the pharyngeal arches [ 27 ]. More recently, we have revealed that non-ectomesenchymal neural crest cell invasion of the second pharyngeal arch is delayed compared with that of the first pharyngeal arch in chicken embryos ( Figure 4 B) [ 70 ]. We also observed HNK1-positive nerve fibers invading the mesodermal core of the pharyngeal arches ( Figure 3 E,F).…”
Section: The Relationship Between Branchiomeric Muscle Progenitors An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, using double in situ hybridization analysis of whole mount chicken embryos, we reported that Sox10 and Ap2α expression can be used to analyze the respective location of neural crest cells in the pharyngeal arches [ 27 ]. More recently, we have revealed that non-ectomesenchymal neural crest cell invasion of the second pharyngeal arch is delayed compared with that of the first pharyngeal arch in chicken embryos ( Figure 4 B) [ 70 ]. We also observed HNK1-positive nerve fibers invading the mesodermal core of the pharyngeal arches ( Figure 3 E,F).…”
Section: The Relationship Between Branchiomeric Muscle Progenitors An...mentioning
confidence: 99%
“…Therefore, an important open question in the field regards when MyHC expression emerges in branchiomeric muscle anlagen. We have recently addressed this question in mouse embryos by analyzing the onset of its expression in the branchiomeric muscles [ 70 ]. MyHC was first detected at embryonic day 10.5 ( Figure 5 A), and its peak expression occurred around embryonic day 13.5 ( Figure 5 D).…”
Section: Branchiomeric Muscles Are Heterogeneous In Terms Of the Onse...mentioning
confidence: 99%